Preventive Principles of Ayurveda with special reference to Seasonal Prophylaxis (International Journal of Ayurveda and Pharma Research, 2023)
Ayurveda the age-old “Science of life” has always emphasized at maintaining health and preventing diseases rather than laying total focus over the treatment aspects. The basic principle followed in the Ayurveda is “Swasthasya swasthya rakshanam” i.e., preventive aspect. Here the importance is given to prevention rather than cure. To maintain health and to prevent diseases various rules and regimens have been told. As Ayurveda has its origin in India, the seasonal changes are observed predominantly in Indian sub-continent. While passing through six seasons our body is bound to face different variations and accordingly it is likely to get affected if the same routine is followed in all seasons. A particular rhythmic pattern of Tri-doshas occur in relation to six seasons. Sanchaya (accumulation), Prakopa (aggravation) and Prashamana (mitigation) of all Tri-doshas takes place when the sun changes from one Rashi to the other. The health impact caused by seasonal variation includes not only physical problems but also physiological changes.